EWSR1-PATZ1-rearranged sarcoma: a report of nine cases of spindle and round cell neoplasms with predilection for thoracoabdominal soft tissues and frequent expression of neural and skeletal muscle markers - Michal, Michael; Rubin, Brian P; Agaimy, Abbas; Kosemehmetoglu, Kemal; Rudzinski, Erin R; Linos, Konstantinos; John, Ivy; Gatalica, Zoran; Davis, Jessica L; Liu, Yajuan J; McKenney, Jesse K; Billings, Steven D; et al. (Modern pathology, 2021)
The knowledge of clinical features and, particularly, histopathological spectrum of EWSR1-PATZ1-rearranged spindle and round cell sarcomas (EPS) remains limited. For this reason, we report the largest clinicopathological study of EPS to date. Nine cases were collected, consisting of four males and five females ranging in age from 10 to 81 years (average: 49 years). Five tumors occurred in abdominal wall soft tissues, three in the thorax, and one in the back of the neck. Tumor sizes ranged from 2.5 to 18 cm (average 6.6 cm). Five patients had follow-up with an average of 38 months (range: 18-60 months). Two patients had no recurrence or metastasis 19 months after diagnosis. Four patients developed multifocal pleural or pulmonary metastasis and were treated variably by surgery, radiotherapy, and chemotherapy. The latter seemed to have little to no clinical benefit. One of the four patients was free of disease 60 months after diagnosis, two patients were alive with disease at 18 and 60 months, respectively. Morphologically, low, intermediate, and high-grade sarcomas composed of a variable mixture of spindled, ovoid, epithelioid, and round cells were seen. The architectural and stromal features also varied, resulting in a broad morphologic spectrum. Immunohistochemically, the following markers were most consistently expressed: S100-protein (7/9 cases), GFAP (7/8), MyoD1 (8/9), Pax-7 (4/5), desmin (7/9), and AE1/3 (4/9). By next-generation sequencing, all cases revealed EWSR1-PATZ1 gene fusion. In addition, 3/6 cases tested harbored CDKN2A deletion, while CDKN2B deletion and TP53 mutation were detected in one case each. Our findings confirm that EPS is a clinicopathologic entity, albeit with a broad morphologic spectrum. The uneventful outcome in some of our cases indicates that a subset of EPS might follow a more indolent clinical course than previously appreciated. Additional studies are needed to validate whether any morphological and/or molecular attributes have a prognostic impact.
Keywords: dospělí; Soft Tissue Neoplasms; Sarcoma; Europe; Female; Phenotype; Repressor Proteins; dítě; represorové proteiny; Adult; výsledek terapie; ženské pohlaví; transkripční faktory Krüppel-like; lidé; Evropa; Gene Fusion; genetická predispozice k nemoci; Aged, 80 and over; Treatment Outcome; Genetic Predisposition to Disease; sarkom; Spojené státy americké; Male; nádorové biomarkery; Aged; protein EWS vázající RNA; United States; fúze genů; Biomarkers, Tumor; lidé středního věku; Child; senioři nad 80 let; nádory měkkých tkání; senioři; mužské pohlaví; fenotyp; Middle Aged; RNA-Binding Protein EWS; Kruppel-Like Transcription Factors; Humans